A Germin-Like Protein GLP1 of Legumes Mediates Symbiotic Nodulation by Interacting with an Outer Membrane Protein of Rhizobia - Zeng, Xiaobo; Li, Dongzhi; Lv, Yanfei; Lu, Yao; Mei, Lingli; Zhou, Donglai; Chen, Dasong; Xie, Fuli; Lin, Hui; Li, Youguo (Microbiology spectrum, 2023)
This study is the first report to characterize a legume host plant protein to sense and interact with an outer membrane protein (OMP) of rhizobia. It can be speculated that GLP1 plays an essential role to mediate early symbiotic process through interacting with OMPs of rhizobia. Rhizobia can infect legumes and induce the coordinated expression of symbiosis and defense genes for the establishment of mutualistic symbiosis. Numerous studies have elucidated the molecular interactions between rhizobia and host plants, which are associated with Nod factor, exopolysaccharide, and T3SS effector proteins. However, there have been relatively few reports about how the host plant recognizes the outer membrane proteins (OMPs) of rhizobia to mediate symbiotic nodulation. In our previous work, a gene ( Mhopa22 ) encoding an OMP was identified in Mesorhizobium huakuii 7653R, whose homologous genes are widely distributed in Rhizobiales . In this study, a germin-like protein GLP1 interacting with Mhopa22 was identified in Astragalus sinicus . RNA interference of AsGLP1 resulted in a decrease in nodule number, whereas overexpression of AsGLP1 increased the number of nodules in the hairy roots of A. sinicus . Consistent symbiotic phenotypes were identified in Medicago truncatula with MtGLPx (refer to medtr7g111240.1 , the isogeny of AsGLP1 ) overexpression or Tnt1 mutant ( glpx-1 ) in symbiosis with Sinorhizobium meliloti 1021. The glpx-1 mutant displayed hyperinfection and the formation of more infection threads but a decrease in root nodules. RNA sequencing analysis showed that many differentially expressed genes were involved in hormone signaling and symbiosis. Taken together, AsGLP1 and its homology play an essential role in mediating the early symbiotic process through interacting with the OMPs of rhizobia. IMPORTANCE This study is the first report to characterize a legume host plant protein to sense and interact with an outer membrane protein (OMP) of rhizobia. It can be speculated that GLP1 plays an essential role to mediate early symbiotic process through interacting with OMPs of rhizobia. The results provide deeper understanding and novel insights into the molecular interactive mechanism of a legume symbiosis signaling pathway in recognition with rhizobial OMPs. Our findings may also provide a new perspective to improve the symbiotic compatibility and nodulation of legume.